Investigating Alumni Performances and Stakeholder Feedback of English Language Teaching Department, IAIN Syekh Nurjati Cirebon: A Tracer Study - Priajana, Nana (Foreign Language Instruction Probe, 2024)
The tracer study conducted by the English Language Teaching Department (ELTD) serves as a pivotal initiative that is aimed at assessing the efficacy of teaching and learning within ELTD at IAIN Syekh Nurjati Cirebon. This comprehensive study endeavors to scrutinize and delve into various facets, including performance and the employability of graduates from tertiary institutions (Higher Education), particularly those from the ELTD at IAIN Syekh Nurjati, upon entering the workforce. It is aimed to gauge the relevance of both hard and soft skills possessed by ELTD graduates, as well as the competencies acquired during their tenure at ELTD. The achievement of graduates in their respective workplaces serves as a significant benchmark for assessing learning outcomes and their alignment with the vision and mission of the English Language Teaching Department at IAIN Syekh Nurjati, both for stakeholders and the broader community. In conducting this research, online questionnaires (utilizing Google Forms) were distributed to alumni and stakeholders, supplemented by in-depth interviews to validate the questionnaire data. The findings of this study shed light on various crucial aspects concerning alumni, particularly regarding the timeliness of job acquisition and the degree of alignment between their fields of work and educational backgrounds.